APLIKASI SISTEM WADAH BERTINGKAT DALAM BUDIDAYA CACING SUTRA DI DESA PUNGPUNGAN BOJONEGORO [APPLICATION OF A RACK CULTURE SYSTEM FOR TUBIFEX WORMS FARMING AT PUNGPUNGAN VILLAGE, BOJONEGORO] - Tuani Lidiawati Simangunsong; Arum Susanti (Universitas Pelita Harapan, 2017)
Fish fry feed mainly on Tubifex worms to ensure its proper growth. From 2 – 15 days after hatching, the fry would be feed Tubifex worms. Thus far, the worms’s supply came from another village so the dependency of Tubifex worms is very high. Tubifex worms had cultured before but the farming was unsuccessful. The harvesting worms hadn’t been able to meet the needs of the fish breeders. One of the causes was the knowledge and skill of Tubifex worms breeders was very low so the failure of Tubifex worms farming was quite high. The community development program was created to overcome the problem. The aims of the program were to ugrade the knowledge and the skill of Tubifex breeders and to improve the quantity and quality of Tubifex worms. There are 3 activities carried out so that the expected goals could be achieved: 1. Workshop of Tubifex worms farming methode 2. Assistance of Tubifex worms farming 3. Providing books or literatures of Tubifex worms farming. The methode of Tubifex farming that was trained to the breeders was a rack culture system. The training material included how to build rack system, water circulation piping and water droplets, preparing worm media and feed, the process of worm quarantine, how to breed Tubifex worm, and the harvesting process. According to the breeders, the system was cheaper and simpler than tray systems that use plastic container, which had been applied before. A rack culture system container was made by utilizing used goods, for example plastic banner and used pond tarps so that the cost could be lower. Farming rack could be made from bamboo or cheap timber that available around neighborhood. The yield of rack system application was able to supply the Pungpungan’s fish breeders more than 30%. The conclusions of this program were 1. Tubifex worms farming using a rack culture system could improve the quantity and quality of Tubifex worms 2. The worms breeder prefered a rack culture system because it was cheaper and easier to apply.